Dispatching the problems in implementing mobile payment services from consumer attitude perspective - Hoang Thien Van; Vo Anh Tien; Huynh Cong Danh; Hoang-Sy Nguyen (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Due to the abundance of internet and e-commerce (electronic commerce), an excessive amount of data has been generated causing an overload of information to the current network infrastructure. As an attempt to solve this problem, there is a shift to mobile payment in the field of E-commerce. Thus, it is essential to study the adoption level of such service for global markets in general and the Vietnamese market in specific. In this paper, we study the consumers' attitude toward mobile payment, investigated with the theory of planned behavior (TPB) from three perspectives, namely the consumer innovativeness, perceived benefit, and perceived risk. Accordingly, there are six hypotheses proposed to study the consumers' attitude toward the service. Thanks to the structural equation modeling (SEM) method, a population of 250 Vietnamese mobile payment users was analyzed to confirm five out of the six hypotheses. It is drawn that the attitude toward the service is correlated positively with the innovativeness and the perceived benefit, while being correlated negatively with the perceived risk. Besides, the resulted model can elucidate approximately 49% the consumers' intention to reuse the mobile payment service.